시스템경비 관제시설의 구축과 보안 및 경영대책 - 하경수(Kyung-Su Ha); 조철규(Cheol-Kyu Cho); 김평수(Pyong-Soo Kim) (韓國컴퓨터情報學會論文誌, 2015)
This research suggests construction processes and security solutions for security control center as management measures for security management improvement in domestic electronic security companies. Security control center (SCC) is the central nerve of electronic security service, and no matter how well the on-site response system has been built, if SCC ceases to work due to an incident or disaster or security control personnel are harmed, the electronic security system cannot perform its proper functions. It is divided to a spatial structure, the infrastructure, control equipment, control solutions and operating structure in a construction process in the security control center. And a solution can be presented for physical security, information security, and personnel security in the way to security solutions. 이 연구는 국내 시스템경비업체의 보안관리 개선을 위한 경영대책의 일환으로 관제시설에 대한 구축 프로세스와 보안관리 방안을 제안한다. 관제시설은 시스템경비의 중추신경으로 현장의 대응체제가 아무리 잘 구축되어 있더라도 관제시설이 장애나 재해로 작동이 중단되거나 관제기계경비원이 위해를 입게 되면 본래의 기능을 수행할 수 없기 때문이다. 관제시설의 구축 프로세스는 공간구조, 기반시설, 관제장치, 관제 솔루션, 운영조직으로 구분하고, 보안관리 방안으로는 물리보안, 정보보안, 인적보안에 대한 대책을 제시한다.